A capability perspective on indigenous autonomy. (2nd July 2016) - Binder, Christina; Binder, Constanze
Abstract: This paper argues that the capability approach can add to the concept of autonomy (as defined in international law) as a means to provide larger freedoms to indigenous peoples. We show that autonomous regimes established within nation-states – by opening up a space for self-governance – provide a means to facilitate indigenous peoples' pursuit of their own paths of development. However, such regimes frequently face, and their effectiveness can be reduced by, various problems such as tensions between individual and collective rights, the definition of the ideal scope of autonomies, and the lack of proper implementation. This is illustrated with case studies from Colombia, Mexico and Nicaragua. We argue that the capability approach, and in particular its focus on the freedom to choose a life path one has reason to value, can be used to address such problems confronting autonomous regimes.